De la Mettrie's Ghost : The Story of Decisions. - Nunn, C. (New York : Palgrave Macmillan, 2005)
A powerful new view of the human brain and free will.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books